2006
DOI: 10.1007/s00125-006-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors, consequences and costs of diabetes-related lower extremity amputation complicating type 2 diabetes: The Fremantle Diabetes Study

Abstract: Aims/hypothesis The aims of this study were to assess the incidence, predictors, consequences, and inpatient cost of lower extremity amputation (LEA) in a community-based cohort of type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
138
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(160 citation statements)
references
References 54 publications
15
138
0
6
Order By: Relevance
“…One possible explanation for this is that patients who underwent a lower leg amputation in the present study were only followed until this amputation was performed, whereas in previous Swedish studies, patients were followed and costs calculated until the amputated leg was completely healed [15,17]. Similarly, the cost of a lower leg amputation reported by the recent Australian study is considerably lower than that reported by the present study, mainly because only inpatient costs were included in their analyses [6]. Patients included in the present study who underwent minor amputations below the ankle, which subsequently healed, were classified as healed patients, whereas the costs of minor amputations were presented separately in the previous Swedish studies [15,17].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…One possible explanation for this is that patients who underwent a lower leg amputation in the present study were only followed until this amputation was performed, whereas in previous Swedish studies, patients were followed and costs calculated until the amputated leg was completely healed [15,17]. Similarly, the cost of a lower leg amputation reported by the recent Australian study is considerably lower than that reported by the present study, mainly because only inpatient costs were included in their analyses [6]. Patients included in the present study who underwent minor amputations below the ankle, which subsequently healed, were classified as healed patients, whereas the costs of minor amputations were presented separately in the previous Swedish studies [15,17].…”
Section: Discussionmentioning
confidence: 58%
“…Studies from Sweden have demonstrated that the cost of treatment for a patient who healed after an amputation were about €29,000-43,000 in the 1990s, depending on the amputation level and whether or not the foot ulcer was infected [3][4][5]. A recent paper on a prospective Australian study reported that, on average, inpatient costs for LEA totalled AU$17,089 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Description of studies Fourteen prospective studies [2,10,12,[20][21][22][23][32][33][34][35][36][37][38] involving 94,640 participants and 1,227 LEA cases were included. Details of study characteristics are provided ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Details of study characteristics are provided ( Table 1). The studies were North American and European, with the exception of two, which were conducted in Australia [38] and Jordan [37]. Three studies [10,22,37] had a nested case-control design, the rest had a cohort design.…”
Section: Resultsmentioning
confidence: 99%
“…This disease affects patients by causing pain, decreased quality of life, falls, ulcerations, and amputations 3, 4, 5. Unfortunately, outside of medications for neuropathic pain, few therapies exist to help patients with peripheral neuropathy 4.…”
Section: Introductionmentioning
confidence: 99%